Effect of Microcrystalline Cellulose Filler on Mechanical and Water Absorption Properties of Ramie/Glass/Carbon Hybrid Laminated Composite - Yudhanto, Ferriawan; Jamasri, Jamasri; Ilyas, Rushdan A.; Terzioğlu, Pınar (American Institute of Physics Inc., 2023)
Hybrid composites laminated (HLC) combined with various types of fibers have less poor interfacial bonding. It is due to the different physical and chemical properties of various fibers used. HLC consists of six layers with a stacking sequence arranged are ramie (R), glass (G), and carbon (C) fiber manufactured by the vacuum infusion process. Adding the microcrystalline cellulose (MCC) 0.5 wt.% into the unsaturated polyester resin (UPE) at 350 RPM for 5 minutes. It increases the tensile strength and elasticity modulus on the HLC with the stacking sequence of CRGGRC by 15% and 34%. The significant effect on flexural strength and elasticity modulus by 47% and 16%. Adding MCC filler inhibits propagation crack in the interlaminar interface of HLC. The addition of MCC filler has a slight impact on water absorption behavior. The water absorption increases by 0.9% on HLC with MCC caused it has hydrophilicity properties.
Keywords: Materials properties; Chemical elements; Crystallography; Polymers; Chemical properties; Carbohydrates